2022
DOI: 10.36312/jolls.v2i1.711
|View full text |Cite
|
Sign up to set email alerts
|

Team Games-Language Learning Model in Improving Students’ Speaking and Listening Skills Viewed from Creativity

Abstract: Speaking and listening are language skills that are supporting each other. Students who have good speaking competence will have good listening skills as well. Unfortunately, students who have good listening skills do not indicate that they have good speaking skills. To help students in improving speaking and listening, this study applied team games-based language learning (TG-BLL) model. This model was designed with appropriate learning materials and activities, and English experts validated the quality of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Therefore, Chan (2021) argues that speaking is fundamentally an instrument act and it needs communicative competence to address ideas to interlocutors. Speakers talk in order to have some effect on their listener (Kenza Tacarraoucht et al, 2022;Nation, 2006;Syarifuddin et al, 2022). It is the result of the language instructional process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Chan (2021) argues that speaking is fundamentally an instrument act and it needs communicative competence to address ideas to interlocutors. Speakers talk in order to have some effect on their listener (Kenza Tacarraoucht et al, 2022;Nation, 2006;Syarifuddin et al, 2022). It is the result of the language instructional process.…”
Section: Introductionmentioning
confidence: 99%
“…The study involved six Focus Group Discussions (FGD) with thirty English language learners from eight universities. Tacarraouch, Zano and Zamorano (2022) showed that new media tools greatly motivated learners, transforming passive learners into active and autonomous learners.…”
Section: Research Questionsmentioning
confidence: 99%
“…The teaching of English aiming to perform good skills by mastering vocabulary encountered problems (Rachmaida & Mutiarani, 2022). Students still have difficulties in understanding English because lack of vocabulary (Chonnia & Izzah, 2022), difficulty in composing sentences (Kenza-Tacarraoucht et al, 2022), difficulty in determining verbs, nouns, adjectives, and adverb (Habibi et al, 2022) as well as difficulty in pronouncing or spelling the correct words (Buana & Irawan, 2021). These problems are performed by English students at the seventh grade students at MTs YP AL-Azhar Medan.…”
Section: Introductionmentioning
confidence: 99%